PENERAPAN PRINSIP “THE BEST INTEREST OF THE CHILD” PADA KEHIDUPAN ANAK YANG TERPAKSA BEKERJA DI INDONESIA - Djehadut, Evans Angokaming; Purwanti, Ni Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
The presence of children who are forced to work in Indonesia creates rules governing restrictions on what jobs that can be done and in what jobs the children were forbidden to work. Related to the principle of "the best interest of the child" which is the primacy of the interests of the child, whether the principle of the protection of children who are forced to work. Therefore, this article will explain what exactly is the purpose of the principle of "the best interest of the child" in the CRC (Convention on the Rights of the Child) and its application for children who are forced to work in Indonesia. In addition, this paper also describes a right or obligation if a child is forced to work.
Keywords: Children, Principle, The best interest of the child, Forced, Work